Determination of Lipids and Glucose Content in Hydatid Cysts of Echinococcus Granulosus Isolated from Different Intermediate Hosts (Sheep, Goats, Cattle And Human) Tissues - Meerkhan, Azad A.; Mero, Wijdan M.S. (Science Journal of University of Zakho, 2013)
This study included comparative biochemical composition of hydatid fluid, protoscolices, infected and non-infected tissues isolated from liver and lungs of infected sheep, goats, and cattle slaughtered in Duhok abattoirs during the period from Nov. 2009 to Apr. 2010. Also hydatid fluid of cysts surgically removed from humans in Azadi Teaching Hospital, Duhok during the period from Mar. 2010 to Jul. 2010. Protoscolices contained higher levels of Lipids, triglycerides and cholesterol with the highest being in cattle liver (63.81±1.434 mg/100g, 38.28±1.277 mgs/100gs and 28.85±0.795 mgs/100gs, respectively) and infected cattle liver and lung tissues (57.78±1.3 mgs/100gs and 51.91±1.299 mgs/100gs, respectively). Hydatid fluid contained high levels of glucose with the highest in hydatid fluid of sheep cysts (Liver: 37.41±0.384 mgs/dl and Lung: 38.98±0.424 mgs/dl) and infected sheep Lung tissues (48.12±0.475 mg/100g).